2015
DOI: 10.1007/s00267-015-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in the Design and Analysis of Biomass Supply Chains

Abstract: The biomass supply chain is one of the most critical elements of large-scale bioenergy production and in many cases a key barrier for procuring initial funding for new developments on specific energy crops. Most productions rely on complex transforming chains linked to feed and food markets. The term 'supply chain' covers various aspects from cultivation and harvesting of the biomass, to treatment, transportation, and storage. After energy conversion, the product must be delivered to final consumption, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Perennials can also be strategically added to sensitive or low-productivity regions within the landscape, such as marginal field sites, riparian buffers, and in-field erosion strips (Bonner, Muth, Koch, & Karlen, 2014;Gopalakrishnan, Cristina Negri, & Salas, 2012;Ha & Wu, 2015;Ssegane, Negri, Quinn, & Urgun-Demirtas, 2015). This incorporation of perennials into the landscape would avoid competition with food production while maintaining economic productivity and providing most of the ecosystem services that would be gained by completely replacing annual crops with perennials (Asbjornsen et al, 2014;Lautala et al, 2015). Feedstock diversity can also improve harvest logistics and reduce overall labor and equipment requirements using the same equipment to harvest multiple feedstocks at different times during the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Perennials can also be strategically added to sensitive or low-productivity regions within the landscape, such as marginal field sites, riparian buffers, and in-field erosion strips (Bonner, Muth, Koch, & Karlen, 2014;Gopalakrishnan, Cristina Negri, & Salas, 2012;Ha & Wu, 2015;Ssegane, Negri, Quinn, & Urgun-Demirtas, 2015). This incorporation of perennials into the landscape would avoid competition with food production while maintaining economic productivity and providing most of the ecosystem services that would be gained by completely replacing annual crops with perennials (Asbjornsen et al, 2014;Lautala et al, 2015). Feedstock diversity can also improve harvest logistics and reduce overall labor and equipment requirements using the same equipment to harvest multiple feedstocks at different times during the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Lautala et al [114] USA 3 Reviewed opportunities and challenges in designing BSC. Important challenges were availability of data; lack of a mutual agenda; and less integrated analysis.…”
Section: Gronalt and Rauch [108]mentioning
confidence: 99%
“…Correspondingly, Busenius et al (2015) showed the reduction of CO2 emissions when using increasing payloads in log transportation. Lautala et al (2015) conclude in their study that "energy consumption, GHG emissions, and overall environmental impacts should be evaluated in unison with logistics costs, as they vary greatly according to transport and logistical decisions made." The authors recommend focussing future research on establishing a common framework allowing the comparison of potential implementations or their impact, improved integration of the supply chain and related analysis, the use of new technologies in transportation logistics and a robust biomass trading market.…”
Section: Discussionmentioning
confidence: 99%